Natural selection and evolution: evolving concepts - Andre J. van Wijnen; Eric Lewallen (Academia Biology)
Many recent studies in evolutionary biology have expanded and refined definitions of biological evolution and natural selection. Current evolutionary models incorporate different adaptive and non-adaptive processes based on molecular genetic changes and how DNA is modified over time in unicellular species, or in germline versus somatic cells in metazoan species. Cogent arguments can be raised for the view that natural selection should be considered a biological law, consistent with quantitative mathematical equations that describe the fitness of individuals, as well as variations within and among populations. Evolution is an overarching framework that incorporates the laws of natural selection and clarifies why phenotypic variation can increase in prevalence and result in species adaptations. The conceptual framework for biological evolution incorporates many cohesive principles that collectively have a predictive value. This framework will continue to evolve with improvements in high-resolution technologies that enable us to examine both adaptive and non-adaptive changes that drive biological phenotypes.